Ảnh hưởng của hình thái, cấu trúc pha của lớp PbO2 kết tủa điện hóa trên nền thép đến khả năng làm việc của điện cực PbO2 trong pin chì dự trữ - Lan, Ngô Thị; Tú, Doãn Anh; Sơn, Lương Trung; Mai Thanh, Đinh Thị (Vietnam Journal of Chemistry, 2016)
In this work, the effects of morphology, phase composition of PbO2 layers on mild steel covered by Fe3O4 film were tested as the role of positive electrodes of lead acid reserve battery Pb| H2SiF6| PbO2. Different parameters such as current density, concentration of lead nitrate, ion H+, temperature of electrolyte were optimized to obtain higher capacity of these electrodes. Maximum capacity was obseverd when the eletrolyte contained 0.75 mol/L Pb(NO3)2, 10-3 mol/L ion H+, current density of 10 mA/cm2, 20 oC. At the current density of 40 mA/cm2, the open circuit voltage was 1840 mV and the maximun voltage was 1720 mV. Keywords. Electrodeposition, PbO2, Fe3O4 film, reserve battery.